Performing opera a practical guide for singers and directors - Ewans, Michael 1946- (Bloomsbury Methuen Drama, 2016)
"In Performing Opera: A Practical Guide for Singers and Directors Michael Ewans provides a detailed and practical workbook to performing many of the most commonly produced operas. Aimed at singers and directors as well as opera lovers, it draws on examples from twenty-four operas ranging in period from Gluck and Mozart to Britten and Tippett, to illustrate exactly how opera functions as dramatic form: how words are illuminated by the composer's music and, in turn, how the singers' movements, expressions, gestures and use of props, together with the costumes and dâecor, present the director's own illumination of both text and music. Grounded in close analyses of performances of thirty scenes and five whole operas by first-rate singers and celebrated directors, Performing Opera provides readers with an appreciation of the unique challenges and skills required by performers and directors. It will assist them in their own performance and equip them with detailed knowledge of works most commonly featured in the repertoire. In the first part of the book the analysis progresses from scenes in which the singers are silent, via arias and monologues, duets and confrontations, up to ensembles. Wider issues are subsequently addressed: encounters with offstage events, encounters with the numinous, characterization, and the sense of inevitability in tragic opera. Each section is supplemented by a series of discussion questions to assist students and teachers, and each chapter contains numerous examples of music and new translations of the texts for the scenes studied"--Provided by publisher.